2020
DOI: 10.1007/s10143-020-01282-7
|View full text |Cite
|
Sign up to set email alerts
|

Is surgery justified for 80-year-old or older intracranial meningioma patients? A systematic review

Abstract: Since the number of elderly people with intracranial meningiomas (IM) continues to rise, surgical treatment has increasingly become a considerable treatment option, even in very old (≥ 80 years old) meningioma patients. Since little is known about whether meningioma surgery in this age group is safe and justified, we conducted a systematic review to summarize the results of surgical outcomes in very old meningioma patients. We performed a systematic literature search in Pubmed, Cochrane Library, and Scopus dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…Finally, an important finding of our study is that patients' co-morbidities have no influence on the effectiveness and especially the toxicity of the treatment, whereas for surgery it is always an issue. A recent review of meningioma surgery in elderly patients [38] often found that postoperative mortality is most commonly associated with co-morbidities. Eksi et al [39] also found in their meta-analysis that co-morbidities are a strong predictor of postsurgical neurologic complications.…”
Section: Toxicitymentioning
confidence: 99%
“…Finally, an important finding of our study is that patients' co-morbidities have no influence on the effectiveness and especially the toxicity of the treatment, whereas for surgery it is always an issue. A recent review of meningioma surgery in elderly patients [38] often found that postoperative mortality is most commonly associated with co-morbidities. Eksi et al [39] also found in their meta-analysis that co-morbidities are a strong predictor of postsurgical neurologic complications.…”
Section: Toxicitymentioning
confidence: 99%
“…Moreover, studies have suffered from factors such as limited sample size [2,13,[15][16][17][18][19]21,22] and short follow-up time [2,15,18,19]. In addition, even though the incidence of spinal meningiomas is highest in the elderly population, there may be a reluctance to operate on these patients due to an expected higher risk of adverse events and poor outcomes [1,[22][23][24][25][26][27][28]. Available studies on this topic have been limited by low patient numbers and lack of a younger control group [21,22,29] (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the population's increasing life expectancy, the finding of intracranial meningiomas in very old patients, i.e. patients that are 80 years old and older, is becoming more frequent [2]. Nowadays, these very old patients with meningiomas often have a good functional status and still live independently at home, despite a known increased frailty [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%